A Human Body Gait Recognition System Based on Fourier Transform and Quartile Difference Extraction - Wang, Xijuan (International Journal of Online and Biomedical Engineering (iJOE), 2017)
<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: DE; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A research method of gait recognition based on feature combination<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> is proposed, which includes the wavelet transform (WT), Fourier transform (FT) and the quartile difference,<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> to explore the<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: DE; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> gait recognition system in Internet of things human body sensor based on <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">smart phone<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: DE; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">.<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> It can extract the low-dimensional gait parameters of the acceleration signal, and these gait parameters can reflect the movement characteristics. <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">Then, they are combined into <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">f<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">eature vector <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">to<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW"> identif<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">y<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW"> by a pattern recognition algorithm.<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">Finally, the experimental verification is carried out in the experimental system.<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> The results show that<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">this <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">gait recognition <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">method <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">simplifies the processing flow to a certain extent, <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">and <span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-TW; mso-bidi-font-weight: bold; mso-ansi-language: ZH-TW; mso-bidi-language: AR-SA;" lang="ZH-TW">improves the recognition accuracy<span style="font-family: 'Times New Roman',serif; font-size: 10.5pt; mso-fareast-font-family: å®‹ä½“; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">. In conclusion, the algorithm has a good effect, and can identify the gait behavior with high precision.